Diverse[city] in the Immaterial Cultural Heritages of Zanzibar Town’s Two Sides - Vyver, Yolanda van der (MAJ - Malaysia Architectural Journal, 2025)
The town of Zanzibar developed on Unguja, the main island of the Zanzibar archipelago in the Indian Ocean off the coast of east Africa. An integral part of Swahili history, Zanzibar Town was the uncontested political, diplomatic, and cultural capital of the Swahili world during the nineteenth century. The town consisted of two parts that were naturally divided by a body of water, a tidal lagoon that separated the old Stone Town with its Omani architecture located on the western triangular peninsula, from Ng’ambo, which means “the other side”, the old Swahili town on the east. The two parts together formed a truly cosmopolitan city, as evidenced by its rich and diverse architecture, religious structures, and multi-ethnic culture. Arab, Swahili, Indian, Persian, Comorian, Goan and Madagascan people lived next to each other on both sides of the creek in wattle-and-daub Swahili houses, Omani beyts and Indian dukas. During the British colonial administration, the cosmopolis was reorganised into a segregated city. Stone Town on the peninsula was subdivided into European, Arab and Indian quarters and Ng’ambo on the mainland became the native sector, to which workers’ quarters were exiled. This theoretical split has survived up to today, creating unique challenges in terms of intangible or immaterial heritage, and when the Stone Town was declared a World Heritage Site in 2000, scholarly interest in the conservation area piqued, to the detriment of Ng’ambo, which was deemed less important. However, the introduction of UNESCO’s Historic Urban Landscape (HUL) approach in 2011 and the publication of the Ng’ambo Atlas in 2019, contributed to the inclusion of both sides in recent scholarly debates and narratives. This article proposes to comment on heritage issues faced by both sides, in the face of growing economic pressures characteristic of emerging economies, and the need for sustainable growth, by applying the HUL approach for the island, postcolonial theory, and the historical research method.